Symbolic Significance of Star Motifs in Islamic Geometric Decoration and Contemporary Trademark Design in Pakistan (Al-Qamar, 2023)
Geometric decoration in Islamic art has a special significance having symbolic meanings. Star motif is one of the most prominent shapes employed in these geometric decorations. These motifs, as they originated with spiritual essence in Persia around nineth century, were carried on as an influential factor in South Asian art, particularly Mughal art. The surface embellishments of the Mughal monuments are flooded with geometries having various types of star motifs. Interestingly, the contemporary trademark design in Pakistan reveals great influence from these geometric star motifs. Having a symbolic significance, these designs create a profound visual impact in communication. This research puts forth the symbolic meaning behind the star used in Islamic geometric decoration, and presents its influence on contemporary visual communication design in Pakistan. The designs studied for this research are the trademarks of banks, universities, government departments, and other private companies and brands. The research, after examining the formal quality of the star motifs with reference to the respective meanings, establishes the significance of star motif in visual communication.
Keywords: Star Motifs; Islamic Art; Geometric Decoration; Visual Communication; Trademark Design; Symbolism